Just add dirt - Bravo, Becky; Moss, Jason (Quezon City Adarna House, Inc., 2009)
Miguel does not like taking a bath. Even if his nanay keeps on reminding him, he runs off to play without taking a bath. One morning, he wakes up to find little plants sprouting from different parts of his body! Will these plants ever stop growing?.
"A book in 2 languages." -- Cover.
This book is recommended for children ages 8 and above.
Text in English and Filipino.
National Children's Book Awards, 2010 Best Reads for Children Winner.
Keywords: Bathing -- Juvenile fiction; Children's stories, Philippine (English); Children's stories, Filipino